Moisture-dependent electrochemical characterization of Ba0.2Sr1.8Fe1.5Mo0.5O6-δ as the fuel electrode for solid oxide electrolysis cells (SOECs) - Kamlungsua, Kittiwat (2020)
Barium-doped strontium ferrite oxide is a double perovskite where Ba dopant replaces A-site cation to give better electrochemical performance by means of lattice expansion, and therefore can potentially be a stable fuel electrode for high temperature solid oxide electrolysis cells. Ba0.2Sr1.8Fe1.5Mo0.5O6-δ 28 (B2SFMO) double perovskite as fuel electrode was prepared by solution combustion synthesis with the calcination temperature of 1100 oC. Three-electrode half cell was used to evaluate its electrochemical performance under various steam contents in hydrogen atmosphere both under fuel cell mode and electrolysis mode. Electrochemical impedance spectroscopy demonstrated that hydrogen oxidation reaction involved gaseous adsorption/desorption, oxide transport, and charge transfer processes whereas the oxide transport process in water reduction reaction was split into faster and slower processes at low steam-content region. Polarization study showed the monotonously decreased current density in SOFC mode with the increase in the steam content but it displayed the opposite trend in the current density in SOEC mode with the suitable steam content at 20%.